Pencahayaan Buatan pada Pendekatan Teknis dan Estetis untuk Bangunan dan Ruang Dalam - Budi Setiawan; Grace Hartanti (Humaniora, 2014)
Lights are essential for humans and other living creatures. Without lights or lighting, surely it will be hard to do everything, especially in the afternoon or at night. As the development of civilization and technology, humans created artificial lighting. For the first time, it was only a substitute for natural light from the sun. Artificial light was provided from the fire; then research and development of the light bulb were conducted by Alessandro Volta, Sir Humphry Davy, Warren De La Rue, to Thomas Alva Edison. After the natural lights from the sun can be replaced by artificial lighting from the lamp, the development of lighting is getting much complex ranging from technical to psychological things. This relates to the increasing human activity in the room. The diversity of different activity requires different types of lighting methods. The development results not only about technical and psychological problems but also aesthetic elements.